FGF Signaling Prevents the Terminal Differentiation of Odontoblasts. (June 2017) - Sagomonyants, K.; Kalajzic, I.; Maye, P.; Mina, M.
Members of the fibroblast growth factor (FGF) family play essential and important roles in primary and reparative dentinogenesis, with conflicting results regarding their effects on odontoblast differentiation. Our recent studies showed that the effects of FGF2 on cells in odontoblast lineage were stage-specific and depended on the stage of cell maturity. Continuous exposure of pulp cells to FGF2 inhibited odontoblast differentiation, whereas early and limited exposure of pulp cells to FGF2 resulted in marked increases in odontoblast differentiation. The purpose of this study was to evaluate the cellular and molecular mechanisms regulating the inhibitory effects of FGF2 on odontoblast differentiation. To do so, we examined the effects of the addition of FGF2 during the differentiation/mineralization phase of the in vitro growth of pulp cultures derived from a series of green fluorescent protein reporter transgenic mice that display stage-specific activation of transgenes during odontoblast differentiation. Our results showed that this treatment first stimulated the differentiation of remaining progenitors in pulp cultures into functional odontoblasts but prevented their differentiation into mature odontoblasts. In addition, this treatment inhibited expression of markers of osteogenesis. Furthermore, we demonstrated that the inhibitory effects of FGF2 on odontoblast differentiation were mediated through activation of FGFR/MEK/Erk1/2 signaling and downregulation of bone morphogenetic protein signaling, with negative and positive roles in the expression of Dmp1 and Dspp, respectively, during the advanced stage of odontoblast differentiation.